ANOVA-Based Analysis of Early Blood Transfusions on Hemodynamics with Severely Injured Trauma Using Bedside Ultrasound Imaging. (22nd July 2021) - Song, Lei; Zhang, Jianguo; Liu, Junliang
Abstract : The focus of the study was to quantitatively analyze the influence of early massive blood transfusions (MBTs) on the hemodynamics and prognostic living quality of patients with severely injured trauma. 114 patients with severely injured trauma were enrolled into MBT group (67 cases) and nonmassive blood transfusions (NBT) group (47 cases) according to whether they accepted MBTs within 24 hours after the admission. All patients had bedside ultrasound technology scanning. Furthermore, the indexes were calculated for inferior vena cava (IVC), peripheral arteries, and heart. The prognostic deaths were recorded. It was found that, in the MBT group, the mortality was lower (7.55% vs. 24.23%) (P < 0.05 ), and these indexes were higher for the IVC expansion (IVCE), the respiration variation index (RVI) of IVC (ΔIVC2 ), the peak flow velocity RVI of brachial artery (ΔVpeakBA ), femoral artery (ΔVpeakFA ), left ventricular outflow tract (ΔVpeakL ), and aorta (ΔVpeakAO ), as well as peak flow velocity time integral RVI of aorta (ΔVTIAO ) (P < 0.05 ). In conclusion, early MBTs can elevate survival rate and prognostic living quality and alleviate the atrophy degree of IVC, peripheral artery, and blood vessel of patients with severely injured trauma. Furthermore, bedside ultrasound scanning demonstrated superb capabilities in quantitatively displaying hemodynamics and outcomes of MBTs of patients with severely injured trauma.